Mindfulness como preditor de felicidade: concepção e teste de um modelo fundamentado em uma abordagem ampliada para o marketing social - Carolina Pantuza Vilar dos Santos (2021)
This thesis proposes a new concept of social marketing based on the purpose of this field of study, which is be the need of social changes for happiness, and defines the promotion of societal well-being as the ultimate goal of social marketing. From the understanding of societal well-being as an holistic happiness, and including in this concept two perspectives of happiness initially conflicting in philosophy and practice, the experiential happiness and the satisfaction with life, a theoretical path model was proposed and tested. This model verified in what measure Mindfulness could link the two happiness promoting possible antecedents common to these two perspectives of happiness. For the test, 1059 online questionnaires were collected containing the validated scales of the latent constructs of the model and sociodemographic and behavioral data of the respondents. A Structural Equation Modeling analysis was performed using IBM SPSS Amos Software, and an analysis by decision tree-based algorithm was executed using Weka Software. The results indicate that Mindfulness can promote a link between aspects of happiness by causing positive effects in Social support, Sense of life and Self-efficacy, and an effect mediated by Self-efficacy and Sense of life in Intentional activities, which seems to be the most significant variable of the model to define levels of happiness in the tested sample. Social support and Intentional activities were confirmed as common antecedents for Experiential happiness and Satisfaction with life. Mindfulness proved to be a predictor of happiness in this model structured in the new proposal for social marketing and can be used as an antecedent of happiness when the diagnosis made by holistic indicators shows that basic structural conditions are not its main obstacle for the population in question. Mindfulness has the potential for social transformation, given that the concept of happiness addressed in this thesis is inherent that of clarity and lucidity in relation to the dynamics of emergence, maintenance and cessation of suffering in society.